Time-dependent scale-free brain dynamics during naturalistic inputs - Klar, Philipp; Çatal, Yasir; Jocham, Gerhard; Langner, Robert; Northoff, Georg (NeuroImage (Orlando, Fla.), 2025)
•Scale-free brain dynamics in sensory regions exhibit a time-dependent spectral exponent in response to naturalistic inputs•This time-dependent spectral exponent positively correlates with time-varying inter-subject correlation in visual and auditory regions•The relative Rest-to-Movie SD change in time-dependent scale-free dynamics modulates the level of time-dependent inter-subject correlation during naturalistic inputs Environmental processes, such as auditory and visual inputs, often follow power-law distributions with a time-dependent and constantly changing spectral exponent, β(t). However, it remains unclear how the brain’s scale-free dynamics continuously respond to naturalistic inputs, such as by potentially alternating instead of static levels of the spectral exponent. Our fMRI study investigates the brain’s dynamic, time-dependent spectral exponent, β(t), during movie-watching, and uses time-varying inter-subject correlation, ISC(t), to assess the extent to which input dynamics are reflected as shared brain activity across subjects in early sensory regions. Notably, we investigate the level of ISC particularly based on the modulation by time-dependent scale-free dynamics or β(t). We obtained three key findings: First, the brain’s β(t) showed a distinct temporal structure in visual and auditory regions during naturalistic inputs compared to the resting-state, investigated in the 7 Tesla Human Connectome Project dataset. Second, β(t) and ISC(t) were positively correlated during naturalistic inputs. Third, grouping subjects based on the Rest-to-Movie standard deviation change of the time-dependent spectral exponent β(t) revealed that the brain’s relative shift from intrinsic to stimulus-driven scale-free dynamics modulates the level of shared brain activity, or ISC(t), and thus the imprinting of inputs on brain activity. This modulation was further supported by the observation that the two groups displayed significantly different β(t)-ISC(t) correlations, where the group with a higher mean of ISC(t) during inputs also exhibited a higher β(t)-ISC(t) correlation in visual and auditory regions. In summary, our fMRI study underscores a positive relationship between time-dependent scale-free dynamics and ISC, where higher spectral exponents correspond to higher degrees of shared brain activity during ongoing audiovisual inputs.